The Impact of Functional Brand Qualities and Intangible Brand Qualities Towards Perceived Value for Millennials in Indonesia - Juniarty Siahaan; Yokie Radnan Kristiyono; Chelsie Gytha Lin (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
Purpose – The role of functional brand qualities of brand innovation and quality and intangible or symbolic brand qualities of brand experience and brand personality are considered key theoretical constructs in branding. However, this study explores and understands the degree of impact that functional brand qualities have on intangible brand qualities and how both functional and intangible brand qualities ultimately contribute to perceived values. Methodology – This study applies the conceptual model to a specific brand within a specified demographic, with Apple being the specific brand. A specific sample of 253 Millennial Apple users between ages 20 to 40 in Indonesia was collected through non-probability judgmental (purposive) sampling. The majorities of respondents are from DKI Jakarta and make up 58.50% of the total respondents. This is seconded by 16.21% of respondents from the Banten province and 13.83% of respondents from West Java. The rest of the respondents are dispersed around Indonesia and are found in other parts of Java, Sulawesi, Sumatra, and Papua. All of the data is processed using SmartPLS ver. 3.3.2 software. Findings – Findings from this research have shown the significance of the direct impact that brand innovation has on perceived quality, brand experience, and brand personality, yet brand innovation does not have much direct impact on perceived value. Moreover, perceived quality also significantly impacts brand experience and perceived value, yet not so much towards brand personality. Brand experience also shows a significant impact on brand personality and perceived value. However, brand personality does not show a significant impact on perceived value Originality – Originality produces new knowledge without repeating what has already been done by others.